Peningkatan Pengetahuan Pelaku Usaha Terhadap Kualitas Proses Produksi dan Penggunaan AI Untuk Pemasaran Produk Halal - Amin Setyo Leksono; Herawati Herawati; Rodiyati Azrianingsih (JURNAL PENGABDIAN PAPUA, 2025)
A community service activity was carried out in Sukosari Village, Kasembon District, to improve the marketing of halal products. However, limited marketing processes have resulted in underdevelopment of food production by MSMEs. Therefore, this Community Service activity aims to improve the knowledge and skills of business actors in implementing Occupational Health and Safety, Clean Production, Marketing Strategies, and the benefits of antioxidants from Kasembon MSME food products. The methods used included location surveys, involving (Paguyuban Destinasi Usaha Kasembon) PADUKA, and continued with education and mentoring. This activity was attended by 10 participants consisting of business actors. Based on the results of the activity, it can be concluded that education/exposure increased the knowledge, motivation, and interest of participants in Kasembon MSMEs. With counseling and training, participants' knowledge and awareness increased. The results of this community service activity show that the knowledge and awareness of the community, especially business actors, regarding the importance of occupational safety, sanitation, marketing strategies and antioxidant content has increased through socialization activities, training, mentoring and monitoring and evaluation. MSMEs have realized the importance of improving marketing through various methods, including using AI (Artificial Intelligence).